CLOTHES ON RESERVATION APPLICATION PROGRAM USING VISUAL TAILOR SAM BASIC 6.0 - Desi Mardianti; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Business couturier on now in great demand by the public despite the apparel industry have a lot, because the couturier business advantages. Where consumers can order a dress in accordance with the size, motives, the desired model, which can not be satisfied by apparel industries.But in this era of globalization, businesses must compete with couturier clothing industry, one of which is an improvement in management and administration system that quickly and accurately so that customer service can be run well and smoothly.